KERJASAMA KEPALA SEKOLAH DENGAN GURU DALAM MEMBANGUN BUDAYA MUTU DI SMK NEGERI 3 SINGKAWANG - Risky Utami; Sukmawati Sukmawati; Wahyudi Wahyudi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to determine the cooperation between principals and teachers in building a quality culture. This research method uses qualitative methods. The research subjects amounted to 4 people, namely the Principal with a male gender aged 53 years, the Deputy Principal for Curriculum Sector with a male gender aged 45 years, the Deputy Principal for Public Relations with a female gender aged 53 years, and teachers senior with male gender aged 48 years. Data collection techniques with interviews, documentation, and observation. Data analysis uses data collection, data reduction, data display and conclusion drawing/verification. Checking the validity of the data used is by triangulation of methods and triangulation of data sources. The results showed that: 1) quality culture planning was carried out in accordance with the quality-oriented school work program in accordance with the National Education Standards (SNP). 2) Implementation of Quality Culture, Implementation of Quality Culture in SMK Negeri 3 according to National Education Standards (SNP), 3) Barriers to the implementation of quality culture, namely facilities and infrastructure, especially for student practice equipment which is still lacking, obstacles in creating a safe environment, beautiful, fun. In addition, obstacles in creating a safe, beautiful and pleasant environment, and 4) Overcoming obstacles in implementing a quality culture, optimizing the use of existing facilities and infrastructure, proposing assistance for facilities and infrastructure to the central government and the education office, procurement of facilities and infrastructure comprehensively. gradually through the allocation of BOS funds and other funds. The conclusion of this study is that the Principal's Collaboration with Teachers in Building a Quality Culture has been carried out well in order to improve the quality of education. The implications of this research can be used as input in improving the quality of education in schools.